Mutual Doings: Exploring Affectivity in Participatory Methodologies - Karin Gunnarsson (Humanities, 2023)
The aim of this paper is to explore the affective implications of working with participatory methodologies within the context of sexuality education. For this exploration, a feminist posthumanist approach is put to work, building on a relational ontology and the notions of affectivity, assemblage and environmentality. Drawing from a practice-based research project concerning sexuality education conducted together with teachers in Swedish secondary schools, the analysis puts forward how the research assemblage navigates and manages affective conditions in ways that produce, allow and exclude certain feelings. With (dis)trust, uncertainty, frustration, laughter and shame, the assemblage made bodies act and become in specific ways. Thus, the analysis shows how participatory and practice-based research become moulded by power relations and intense flows of desire working together. This raises questions about how participatory methodologies within an ontological view of interdependence afford to manage affective intensities to move in certain directions of socially just sexuality education.